'Stay Safe-Feel Positive' on the frontline: An online positive psychology intervention for police officers during the COVID-19 pandemic. Issue 6 (2nd November 2022) - Brouzos, Andreas; Vassilopoulos, Stephanos P.; Romosiou, Vasiliki; Stavrou, Vaia; Tassi, Christina; Baourda, Vasiliki C.; Brouzou, Katia Ourania
ABSTRACT: The current study investigated the effectiveness of an online Positive Psychology group intervention for police officers intending to mitigate the psychological impact of the COVID-19 pandemic and to enhance their personal strengths and resilience. Participants were 95 Greek police officers, assigned to the intervention ( n = 49) and the control ( n = 45) group. All participants completed an online questionnaire at four time-points. The results indicated a significant increase in the intervention group's empathy, resilience, and positive emotions, as well as a significant decrease in fear of the coronavirus, negative emotions, loneliness, depressive symptoms and anxiety emotions compared to the control group. Changes remained significant in the long-term. The intervention assisted police officers in developing their personal strengths in a difficult period, indicating that personal growth can be triggered even in adverse situations.